MPox Skin Lesions - Robert Sinto; Alvin Johan; Hanny Nilasari; Evy Yunihastuti; Erni J Nelwan (Interna Publishing, 2024)
Mpox is caused by the Monkeypox virus, which belongs to the Orthopoxvirus genus and Poxviridae family. The Monkeypox virus was first identified as a cause of disease in humans in the 1970s in the Democratic Republic of the Congo. Mpox was considered endemic in several African countries. A global outbreak of Mpox was first recognized in Europe in May 2022 and was declared a public health emergency of international concern on July 23, 2022. The first reported Mpox case in Indonesia was in October 2022 which was identified as an imported case, there were no new confirmed Mpox cases until 13 October 2023. Since then there were 72 cases of confirmed Mpox cases in Indonesia by the end of 2023, distributed across 6 provinces, mostly in the Java island. We present two different spectrums of Mpox skin lesions in patients living with HIV, with a positive polymerase chain reaction test for Mpox. The first patient is a 48-year-old male, who developed a maculopapular lesion, that was initially noticed on the face, the lesions were then spread to the back and hand. He identifies as men who have sex with men and living with HIV for the past 18 years. There were no lesions on the genitalia or mucosa. The second patient is a 28-year-old male, the initial symptom was fever, followed by skin lesions after around 1 week of fever. The lesion initially appears as pustules on the face and then spreads throughout the whole body, the lesions also grow larger and become pseudo-pustules and ulcers. There were also mucosal involvements in the mouth, making oral intake difficult. This patient also identified as men who have sex with men with multiple partners, HIV status was not known at the initial presentation. HIV screening was done with positive results.